ACANTHOCEPHALAN PARASITES 0F CERTAIN FISHES FROM MANIPUR, INDIA: ONE KNOWN SPECIES OF GENUS PALLISENTIS AND ONE NEW SPECIES OF GENUS ACANTHOCEPHALUS - SHOMORENDRA, M.; RANIBALA, TH.; JHA, A.N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The present investigation deals with the description of one known species, Pallisentis ophiocephali (Thapar, 1930) Baylis, 1933 from fish host Chaniia ,ctriatzis (BI.) from a new locality and description of one new species, Acanthocephahislokiakensis from fish host Channagachua (Ham.). A. Ioktakensis differs from all species of the genus Acanthocephalus in the size proboscis hooks and size of roots of hooks. The hooks-increase in size tìoni the apex towards the middle and thence gradually decrease towards the base.